2022
DOI: 10.1002/brb3.2586
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and fear among Iranian medical students due to COVID‐19: An observational study

Abstract: Introduction The coronavirus disease of the 2019 (COVID‐19) pandemic has created a sense of fear due to uncertainties in medical students’ personal and professional lives. Medical education is challenging and poses a more significant academic and emotional rigor when compared with other professional programs. With the COVID‐19 having limited treatment options, health literacy (HL) is crucial for managing and responding to the pandemic. This research aims to examine the impact of HL on COVID‐19‐associated fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The Chinese questionnaire was utilized as provided by the COVID-HL Network Survey on university students. 26 , 30 Data were gathered on sociodemographic characteristics, subjective social status, information satisfaction, the importance of online information searching, fear of COVID-19, DHL, and well-being.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese questionnaire was utilized as provided by the COVID-HL Network Survey on university students. 26 , 30 Data were gathered on sociodemographic characteristics, subjective social status, information satisfaction, the importance of online information searching, fear of COVID-19, DHL, and well-being.…”
Section: Methodsmentioning
confidence: 99%
“… 20 , 25 A study in Pakistan indicated that 54.3% of the students had high DHL score, and gender, sense of coherence, and importance of information were associated with higher DHL score. 26 Another study showed that DHL was positively associated with psychological well-being. 27 …”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The corona virus disease (COVID-19) pandemic, with its unique stressors like virus fear, financial uncertainty, and social isolation, has notably impacted sleep patterns worldwide. [3,4] Previous studies have underscored the prevalence of sleep disorders during this period, highlighting the influence of global and cultural factors in understanding these disturbances. [5,6] Another study emphasizes the importance of sleep in preserving life and improving our overall quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The government has opened many emergency hospitals with limited hospitals, but additional personnel is also needed ("RS Darurat," 2020). In addition, residents had been reallocated from their preliminary rotations to the emergency department, in-depth care unit, and Covid-19 ward to fulfill the demand of medical personnel (Fong et al, 2020) In addition, these medical residents also experienced fear during the uncertainty and their duties to provide services to patients suffering from Covid-19 (Pourfridoni et al, 2022;Terzic-Supic, 2021).…”
Section: Introductionmentioning
confidence: 99%